George Orwell, Internment and the Illusion of Liberty. Issue 2 (1st September 2014) - Robinson, Emma
Abstract : George Orwell's initial response to wartime internment is characterised by his silence. Uncertainty, desire for government work, wartime necessity, political prejudice and faith in English reasonableness contributed to his toleration of the policy, in the specific context of total war. Orwell worried that criticising internment could undermine public trust in civil liberties, which performatively protected England from the excesses of totalitarianism. Unlike others on the Left, he therefore placed his faith not in the vigilance of parliament, but in an illusion embraced by the English people: that they remained guardians of civil liberties, despite a need in wartime to curtail them.